Using Local Anesthesia for Burr Hole Surgery of Chronic Subdural Hematoma Reduces Postoperative Complications, Length of Stay, and Hospitalization Cost: A Retrospective Cohort Study From a Single Center - Zhuang, Zerui; Chen, Zelin; Chen, Hui; Chen, Bin; Zhou, Jianzhi; Liu, Anmin; Luo, Jianming (Frontiers in Surgery, 2022)
Purpose: The purpose of the current study was to compare the effects of local anesthesia (LA) and general anesthesia (GA) on the surgical process and postoperative recovery of patients with unilateral chronic subdural hematoma (CSDH). Patients and Methods: A retrospective cohort study was conducted on patients with unilateral CSDH who underwent burr hole surgery between the years 2013 and 2018. Patients who received local anesthesia were allocated to the LA group, and the patients who received general anesthesia were allocated to the GA group. The clinical data, postoperative complication, length of stay, and hospitalization cost of these two groups were compared and analyzed. Results: Data from 105 patients was collected for this study. 51 patients were assigned to the LA group and 54 to GA group. The duration of anesthesia and operation of the LA group was 37.71 (10.55) minutes; while for the GA group the duration was 56.04 (8.37) minutes (p < 0.001). The time from operation to discharge in GA group was greatly longer than that in LA group [(8.51 (1.49) days vs 10.46 (2.34) days, respectively; p < 0.001]. Hospitalization cost for LA group was 2721.54 (504.66) USD, which was significantly lesser than that for GA patients [3314.82 (493.52) USD; p < 0.001]. The total number of complications in LA patients was less than that in GA patients [6 vs 29 cases, respectively; p < 0.001]. The number of patients with residual hematoma in the LA group was less than that in the GA group (p = 0.014). Conclusion: As compared to GA, LA might be a simpler, safer, and more effective method for burr hole surgery of CSDH to promote patients’ recovery. However, further research is still required to confirm this conclusion.